Regional Stakeholders in the COVID-19 Crisis – Problems and Challenges - Joanna KUDEŁKO; Karol WAŁACHOWSKI; Dariusz ŻMIJA (Communications of International Proceedings, 2021)
The crisis triggered by the COVID-19 pandemic revealed the shortcomings and weaknesses of regional economies. It should therefore be perceived as an impulse for change, aimed at building greater resilience to various external shocks, which will also occur in the future. The aim of the paper is to identify the problems and challenges faced by various stakeholders of regional economies, appearing in the face of the COVID-19 crisis, and ways of overcoming them. Our research shows that the necessary values to be strengthened in order to create a modern and resilient regional economy include competences, scientific and technological knowledge, financial capital and public and social security. We find that to strengthen the priority values, the specific styles of actions should be adopted, which would enable effective use of endogenous potential resources of the region. These include flexibility, diversification and communication and cooperation. The Authors employ the method of scientific analysis and deduction, they refer to their own observations of socioeconomic phenomena and critically analyze literatures and strategic documents.
Keywords: COVID-19 Crisis; Regional Stakeholders; Vulnerability of Regional Economies.